Effects of olympic style taekwondo kicks on an instrumented head-form and resultant head injury measures. Issue 4 (27th March 2011) - Fife, G; Pieter, W; O'sullivan, D; Cook, D; Kaminski, T
Abstract : Background: In taekwondo (TKD), concussion incidence is four times greater than in American football. Biomechanical investigations on concussion in TKD is sparse. Objective: To examine differences in TKD kicks on resultant head linear acceleration (RLA), head injury criterion (HIC15) and peak head velocity (HVEL). Design: Between-groups. Setting: Biomechanics laboratory. Participants: 12 elite male TKD athletes (22.5+3.5 years, 176.9+7.3 cm, 70.9+8.6 kg). Interventions: Five head kicks (round kick (RK), front leg axe kick, clench-axe kick (CA), jump spin back kick, jump spin hook kick (JH)) were randomly performed five times each. A Hybrid II Crash Dummy head (H2D) was instrumented with a tri-axial accelerometer (PCB Piezotronics-356A66) mounted inside the H2D head. The H2D was fixed to a height adjustable frame and fitted with a protective TKD helmet. Acceleration data were captured using Qualisys Track Manager (Gothenburg, Sweden) and processed in accordance with SAE J211-1. Main outcome measurements: RLA, HIC and HVEL. Results: The RK (130.11±51.67 g) produced a higher RLA than the CA (54.95±20.08 g, p<0.001, d=1.84) and a higher HIC15 than the JH (672.74±540.89 vs 300.19±144.35, p<0.001, ES=0.97). The range of the RLA by the RK was 60.50–217.33 g, while the CA was 26.34–99.02 g. The HIC15 range for the RK was 128.40–1608.70 and the JH, 63.90–573.00. There was no difference in HVEL of the RK (4.73±1.67 m/s, range: 3.36–9.52 m/s) and that of the JH (4.43±0.78 m/s, range: 3.00–5.54 m/s) (p=0.977, ES<0.01). Conclusion: Our investigations are the first to identify the high-magnitude head impacts in TKD. A previous report suggests an HIC15 concussion threshold of >200. The RK is of concern because it is the most common technique and most common cause of concussion in TKD and has a high RLA and HIC15. Prevention of concussion in TKD should focus on employing qualified medical personnel, injury monitoring, and safer equipment.